Realized genetic gain for yield and yield attributes in groundnut breeding at ICRISAT from an ERA trial - Behera, Partha Pratim; Deshmukh, Dnyaneshwar; Vemula, Anil Kumar; Bangaru, Kiranmayee; Bagudam, Rachana; Mathew, Anurag; Purohit, Ashutosh; Vishnumolakala, Aparna; Wankhade, Ankush P.; Kounain, Safinaaz; Guguloth, Nehru; Variath, Murali T.; et al. (Frontiers Media, 2025)
Introduction: Groundnut or peanut (Arachis hypogaea L.) is an important food and oilseed crop with a global production of >50 m t from ~34 m ha. The ICRISAT groundnut breeding program, established in 1976, has significantly contributed to varietal development, resulting in the release of >240 varieties in 39 countries. Estimating realized genetic gain (RGG) in a breeding program helps to measure the progress made for agronomic traits and identify gaps to guide the breeding strategy.